1)
Давайте упростим шаг за шагом.
81− (c − d)^2
Распространять:
= 81 + −c^2 + 2cd + −d^2
ответь:
= −c^2 + 2cd − d^2 + 81
2)
м^2− (м + п)^2
= m^2 + −m^2 + −2mn + −n^2
Объедините похожие термины:
= (m^2 + −m^2) + (- 2mn) + (- n^2)
= −2mn + −n^2
= −2mn − n^2
1)
Давайте упростим шаг за шагом.
81− (c − d)^2
Распространять:
= 81 + −c^2 + 2cd + −d^2
ответь:
= −c^2 + 2cd − d^2 + 81
2)
Давайте упростим шаг за шагом.
м^2− (м + п)^2
Распространять:
= m^2 + −m^2 + −2mn + −n^2
Объедините похожие термины:
= m^2 + −m^2 + −2mn + −n^2
= (m^2 + −m^2) + (- 2mn) + (- n^2)
= −2mn + −n^2
ответь:
= −2mn − n^2